Effectiveness of Guided Imagery on Stress and Coping among Wives of Alcoholics : A Systematic Review - Aarti1 , Srinivasan P2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Alcoholism is one of the major health as well as social problem all over the world today. Alcoholism is a family problem, it causes stress in the relationship and misuse affects couples’ relationship in a variety of negative ways. Purpose: To systematically review articles to evaluate the effectiveness of Guided Imagery on Stress and Coping among Wives of Alcoholics in selected De-addiction centre. Method: The search of significant articles including effectiveness of Guided Imagery on Stress and Coping among Wives of Alcoholics was carried out in PubMed/ Medline, and Google Scholar. The included studies both qualitative and quantitative were evaluated according to predefined quality criteria. Medline and PubMed were searched to identify peer-reviewed English-language studies published between 1985 and March 2018 reporting on stress and coping among wives of alcoholics. Total 300 studies were selected for review, out of which only 32 were found appropriate to be included in the study. Results: Analysis was done 90 papers were retrieved by the search. Among them, 30 were evaluated to be of higher quality. Studies recruiting sample of wives of alcoholics and excluded wives of non-alcoholics. Conclusion: Based on the review it was concluded that Wives of alcoholics had more stress and social disabilities which were directly related to the severity of husband’s drinking pattern. Wives of alcoholics have highest rate of personality and emotional disturbance. Working women faced lesser stress as compared to non-working women. Wives of alcoholics had poor coping skills. They used maladaptive coping behavior to cope up with their husband’s drinking problem such as but not limited to discord, fearful withdrawal and avoidance were commonly used maladaptive coping behaviors. Relaxation therapies were found to be effective to reduce stress and in improving coping. Guided imagery was very effective in reducing stress and improving adaptive coping among wives of alcoholics.